Case report: Ileocecal preservation for multiple small intestinal duplications - Xu, Hongxiu; Liu, Weiqiang; Liu, Chunqing; Zhai, Yunpeng; Zhao, Huashan; Guo, Rui; Lv, Longfei; Zhang, Shisong (Frontiers in Pediatrics, 2023)
Small-intestinal duplication is a rare congenital developmental anomaly that is mainly single; multiple small-intestinal duplications are rare. Most malformations are located in the ileocecal region. The primary surgical treatment is complete resection of the malformations and adjacent intestinal ducts. However, the ileocecal junction plays an important role in children, and it is difficult to preserve it; multiple intestinal repairs increase the risk of postoperative intestinal fistula, which is a challenge for pediatric surgeons. Herein, we report a case of ileocecal preservation surgery for the treatment of multiple small intestinal duplication malformations near the ileocecal area. The child underwent laparoscopically assisted cyst excision and multiple intestinal repairs and had good postoperative recovery and follow-up.